2011
DOI: 10.1371/journal.pone.0016615
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK-Mediated Bmi-1 Down-Regulation and Defective Proliferation in ATM-Deficient Neural Stem Cells Can Be Restored by Akt Activation

Abstract: A-T (ataxia telangiectasia) is a genetic disease caused by a mutation in the Atm (A-T mutated) gene that leads to neurodegeneration. Despite an increase in the numbers of studies in this area in recent years, the mechanisms underlying neurodegeneration in human A-T are still poorly understood. Previous studies demonstrated that neural stem cells (NSCs) isolated from the subventricular zone (SVZ) of Atm -/- mouse brains show defective self-renewal and proliferation, which is accompanied by activation of chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 35 publications
5
36
0
Order By: Relevance
“…3pk is not the only kinase reported to phosphorylate BMI1. Kim et al [2011] recently demonstrated that epidermal growth factor (EGF)-induced Akt activation phosphorylated BMI1 and that this modification renders BMI1 resistant to proteasomal degradation, leading to its stabilization and accumulation in the nucleus. Quantitative analysis of the human spindle phosphoproteome revealed that three serine residues (S251, S253, and S255) at the C-terminal of the BMI1 protein were phosphorylated in extracts from HeLa cells [Malik et al, 2009].…”
Section: Post-translational Regulation Of Bmi1mentioning
confidence: 99%
“…3pk is not the only kinase reported to phosphorylate BMI1. Kim et al [2011] recently demonstrated that epidermal growth factor (EGF)-induced Akt activation phosphorylated BMI1 and that this modification renders BMI1 resistant to proteasomal degradation, leading to its stabilization and accumulation in the nucleus. Quantitative analysis of the human spindle phosphoproteome revealed that three serine residues (S251, S253, and S255) at the C-terminal of the BMI1 protein were phosphorylated in extracts from HeLa cells [Malik et al, 2009].…”
Section: Post-translational Regulation Of Bmi1mentioning
confidence: 99%
“…We and two other groups 6,65,66 have reported that BMI1 is phosphorylated by PI3K-AKT signaling, although the consequences of phosphorylation on BMI1 function varied between these reports. Kim et al .…”
Section: Regulation Of Histone-modifying Enzymesmentioning
confidence: 87%
“…50μM) of gemcitabine could inhibit Bmi1 expression (data not shown), which might account for the reduced Bmi1 staining of tumor tissues in nude mice received high gemcitabine chemotherapy. Gemcitabine has been proved to exert different effects on pancreatic cancer cells in a dose and time dependent manner by inducing different signaling pathways [21, 27], whereas Bmi1 expression can also be affected by such specific signaling molecules [28]. Thus, it is tempting to speculate that different signaling pathways induced by low or high concentrations of gemcitabine treatment may exert promoting or inhibiting role on Bmi1 expression in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%